2014
DOI: 10.15517/rbt.v54i2.13870
|View full text |Cite
|
Sign up to set email alerts
|

Epiphytic dinoflagellates associated with ciguatera in the northwestern coast of Cuba

Abstract: The spatial and temporal abundance of epiphytic dinoflagellates associated with ciguatera was studied over two annual cycles (March 1999 to March 2000 and March 2001 to March 2002) in the northwestern coast of Cuba. From 14 species of macroalgae (Phaeophyta, Chlorophyta, and Rhodophyta), 1340 samples were obtained identifying seven species as potentially noxious; five of them are new reports for Cuba's phytobenthos: Prorocentrum belizeanum Faust, P. concavum Fukuyo, P. mexicanum Tafall, Coolia monotis Meunier,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 10 publications
5
30
0
6
Order By: Relevance
“…In contrast, Parsons and Preskitt (2007) surveyed seven sites in Hawaii and found that salinities from $27 to 33 were equally conducive to Gambierdiscus growth. Additional studies have noted that Gambierdiscus cells are excluded from the rainy (lee) side of many islands, near river mouths and elsewhere when salinities are low (Yasumoto et al, 1980;Taylor and Gustavson, 1986;Delgado et al, 2006). However, the magnitude of the salinity change necessary to limit Gambierdiscus abundance remains uncertain (Carlson and Tindall, 1985;Taylor, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Parsons and Preskitt (2007) surveyed seven sites in Hawaii and found that salinities from $27 to 33 were equally conducive to Gambierdiscus growth. Additional studies have noted that Gambierdiscus cells are excluded from the rainy (lee) side of many islands, near river mouths and elsewhere when salinities are low (Yasumoto et al, 1980;Taylor and Gustavson, 1986;Delgado et al, 2006). However, the magnitude of the salinity change necessary to limit Gambierdiscus abundance remains uncertain (Carlson and Tindall, 1985;Taylor, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…On the western side, studies were carried out on the Belize coast (e.g. Faust & Gulledge, 2002;Faust, 2009), and around Mexican and Cuban coasts (Hernández-Becerril & Almazán Becerril, 2004;Delgado et al, 2006). The southern Caribbean sea has only been investigated by Grzebyk et al (1998) who collected samples from a Panamanian island and Rodriguez et al (2010) who made a survey at San Andrés Island (Caribbean Colombia).…”
Section: Introductionmentioning
confidence: 99%
“…Again, laboratory experiments report species-specific and strain-specific responses to salinity ranges. In the field, maximum cell abundances are found at salinities of 30 to 39, and are very low in river plumes (salinity values 25-35; e.g., Delgado et al, 2006;Blanfuné et al, 2015). However, because low salinities are associated with land runoff and potential nutrient supply, discrimination of the individual roles of these two factors is difficult.…”
Section: Understanding Habitat Preferences and Ecological Linksmentioning
confidence: 99%